Management of fracture non-union long bones by limb reconstruction devices - Praveen Garg; Bajpai, Tanmay; Rajeev Saxena (Asian Journal of Medical Sciences, 2022)
Background: The limb reconstruction system (LRS), rail road fixator, and Ilizarov fixator are used to treat open fractures with bone loss and infective non-union of long bones. It benefits the fracture site by permitting distraction, compression, and further enhancing micromotion at the level of fracture site which plays an important part in healing. The LRS is a straightforward, unidirectional arrangement that provides exceptional strength and rigidity. The limb rebuilding procedure has proven to be an effective treatment option in instances of fracture infective non-union of long bones. Aims and Objectives: This study is to evaluate and to observe the use of limb reconstruction devices (such as the Ilizarov fixator and the rail road fixator) in the treatment of open fractures with bone loss and infective non-union of long bones. Materials and Methods: Twenty patients (15 males and five females) with fracture non-union of long bones were involved in this study after taking permission from ethic committee and consents from all 20 individuals. These patients then underwent thorough debridement and resection of non-viable bone ends with the application of limb reconstruction devices which were then followed by bone transport to fill the bone gap. This was done by means of Ilizarov in 13 patients and by rail road fixator in the remaining seven patients. The average time of union and complications were evaluated. Results: Mean duration of fracture union was 7.9 months. While one patient had failure resulting in non-union, other 19 patients achieved union by limb reconstruction devices. Majority of the cases had no complications. Mean period of hospital stay for Ilizarov was 68.13 days and for rail road fixator 53.17 days. After applying independent “t-test,” no statistically significant differences were observed in fracture union duration between Ilizarov and rail road fixator, since the calculated P value was observed to be >0.05. Mean union of Ilizarov and rail road fixator application was found to be 7.6 months and 8.2 months, respectively. Conclusion: Limb reconstruction devices in our present study can be utilized as an effective way to tackle infective non-union of long bones and open fracture with bone loss for achieving better stabilization. Both Ilizarov and rail road fixator perform a crucial role in causing early mobilization of the patient and also in fracture union by distraction osteogenesis.